2019
DOI: 10.1080/2162402x.2018.1561119
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from GM-CSF expressing embryonic stem cells are an effective prophylactic vaccine for cancer prevention

Abstract: The antigenic similarity between embryos and tumors has raised the idea of using embryonic material as a preventative vaccine against neoplastic disease. Indeed, we have previously reported that a vaccine comprises allogeneic murine embryonic stem cells (ESCs) and murine fibroblasts expressing GM-CSF (to amplify immune responses) successfully blocks the outgrowth of an implantable cancer (Lewis lung carcinoma; LLC) and lung tumors generated in mice using a combination of a mutagen followed by chronic pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 49 publications
2
34
2
Order By: Relevance
“…Thus, exosomes from cultured cell media may represent an effective way to develop vaccines based on maturing DCs, even if recent data suggest that there is probably a synergic effect between vesicular and soluble molecules [157]. Considering the recent activation of anti-WT1 vaccine clinical trials for AMLs [158,159] and the results reported for antitumor vaccines [160], exosome-based vaccines are expected to be widely explored in the future, and the upcoming results would hopefully impact the way we manage AML cases.…”
Section: Small Evs As Potential Therapeutic Toolsmentioning
confidence: 99%
“…Thus, exosomes from cultured cell media may represent an effective way to develop vaccines based on maturing DCs, even if recent data suggest that there is probably a synergic effect between vesicular and soluble molecules [157]. Considering the recent activation of anti-WT1 vaccine clinical trials for AMLs [158,159] and the results reported for antitumor vaccines [160], exosome-based vaccines are expected to be widely explored in the future, and the upcoming results would hopefully impact the way we manage AML cases.…”
Section: Small Evs As Potential Therapeutic Toolsmentioning
confidence: 99%
“…Similarly, EVs derived from immune cells contain many functional molecules and mediate communication among immune cells ( 43 , 50 – 54 ). Additionally, EVs from embryonic stem cells also possess some antigens similar to those from cancer cells ( 31 ). All immunosuppressive and immunostimulatory cargo in EVs discussed in this review are listed in Tables 1 , 2 , respectively.…”
Section: Immune Cargo Of Evsmentioning
confidence: 99%
“…Common antigens between tumor and embryonic cells are the immunological basis for using embryonic cells as antitumor vaccines ( 98 ). An interesting attempt was conducted to stimulate antitumor immunity by using exosomes from ESCs, which may express similar carcinoembryonic antigens as some tumor cell types ( 31 ) ( Figure 3A ). Vaccination with exosomes from granulocyte-macrophage colony-stimulating factor (GM-CSF)–expressing murine embryonic stem cells could prevent the growth of implanted LLC lung adenocarcinoma, B16-F10 melanoma, MC-38 colon adenocarcinoma, and 4T1 mammary carcinoma but not E0771 medullary breast adenocarcinoma in allogeneic mice ( 31 ).…”
Section: Associated Therapeutic Applications Of Evs In Lung Cancermentioning
confidence: 99%
See 2 more Smart Citations